Sistem Komunikasi Politik Libertarian Di Indonesia (Studi Kasus Program Indonesia Lawyer Club (ILC) TVONE) - Hanafi Hanafi (Universitas Informatika dan Bisnis Indonesia, 2019)
This paper aims to find, find out various data and information about the attractions of political communication in Indonesia (the case of the Indonesia Laweyer Club (ILC) Tv-ONE program. this is a type of qualitative research using descriptive methods based on observation and literature studies, the results that can be explained that the program cared for by senior journalist Karni Ilyas is so free and free to display a variety of discussion themes, both concerning legal issues, ideology, politics, economics, social culture, military, etc. This program is packaged in a straightforward, transparent, and even blunt manner with regard to state affairs in various fields above TV One itself as one of the national private media in Indonesia, appeared together with the euphoria of extraordinary freedom. from various the rest of this ILC program implies the attraction of political communication that fulfills its characteristics as a libertarian media.